ABOUT DIPLOMATIC LAW CONCEPT AND SOME EVOLUTION ASPECTS - Лобжанідзе, Гіві Шалвович; Лобжанідзе, Давид (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
The purpose of the article the research of the diplomatic law is interesting from the standpoint of determination the interstate order and international relations to define the political differences and mistakes. This research helps us to determine in what way the state uses the diplomatic and legislative language in relation with the other states, how the documents are written and what are the future results. Research methods: the use of the system-structural method and the method of generalization allowed us to analyze the general tendencies of the use of analytical methods. The dialectical method of scientific cognition, as well as methods of analysis, synthesis and abstraction, clarified the content and purpose of the problem under study, identified its main features and structure, as well as the relationship with system analysis. Results: thus in conclusion the research of diplomatic and consulate law is interesting from the standpoint that it is a measure of balance between interstates’ order and international relations to define the differences and mistakes to study how the state uses diplomatic and legislative languages with others states, in which way the diplomatic rules are defined and followed, how the documents are written and what results can cause all these above mentioned elements. Discussion: we must take into consideration that through the diplomatic ways 1. The communication is not a guarantee for incorrect views. 2. The message can be directed to the second party respond – if we help them to estimate the situation in such way that correspond their values and targets. In these details may be a possibility for success